(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A documentary review of the scientific production registered in the Scopus database on the study of Digital Distance Education in the COVID-19 pandemic in Latin America was carried out with the purpose of knowing the main characteristics of the generation of new knowledge on this topic. The information analyzed is provided by Scopus through its Search tool, by means of which the data is filtered in such a way that a total of 178 research papers published in high impact journals are obtained, referring to distance education during the COVID-19 pandemic. Due to its nature, the temporal delimitation is defined by the two semesters of 2020 and the first semester of 2021, at the date of the present research. The bibliometric review is performed on the basis of these data, which are classified according to their area of knowledge, country of origin and affiliation. Once the information is classified, certain papers are analyzed from a bibliographic perspective to know and define the position of different authors with respect to the proposed topic.